Producing and understanding conditionals: When does it happen and why does it matter? - Badger, J; Mellanby, J (Science-res Publishing, 2018)
Comprehending complex conditional sentences plays an integral part in understanding many aspects of learning at school, particularly in subjects such as science and history, where hypotheses and alternative explanations are important. While simple conditionals are produced by pre-school children, the acquisition of complex conditionals occurs later. This cross-sectional and longitudinal design investigated the trajectory for production and comprehension of type II and type III conditionals in two cohorts of children, one starting in January of year 1 (age 5-6; n=225), the second in January of year 2 (age 6-7; n=292), with three measurement points over a 9 month period. Production was measured using a repetition task, comprehension by providing conditional sentences and asking the children to say whether four statements about each sentence were true. Single word reading and verbal and non-verbal ability were also measured. Production occurred much earlier than comprehension. By the start of year 3, 71% of children could repeat type II sentences and 52% could repeat type III sentences. In contrast, at the same point, fewer than 20% of children could understand either type II or type III conditionals. Logistic regressions showed that while production of type III conditionals predicted comprehension of both type II and type III conditionals 9 months later, comprehension of type II was also predicted by single word reading while type III comprehension was also predicted by ability. Acquisition of conditionals is likely to play an important role in academic success. The results are discussed with respect to the importance of understanding conditionals for academic success.